Nanosuspension: A Novel Drug Delivery System - Ganesh, Bhatt; Ankita, Raturi; Preeti, Kothiyal (International Journal of Pharmaceutical and Life Sciences, 2013)
Low bioavailability is the major problem associated with poorly soluble drugs. The problem is more complex for drugs which are poorly soluble in both aqueous and nonaqueous media, as solubility is an essential factor for drug absorption, independent of the route of administration. Nanosuspensions have emerged as an attractive and promising approach to improve stability and bioavailability of poorly soluble drugs. These are very finely colloid, biphasic, dispersed, solid drug particles in an aqueous vehicle, size below 1?m, without any matrix material, stabilized by surfactants and polymers. Techniques such as wet milling, high-pressure homogenization, emulsification-solvent evaporation and supercritical fluid have been used in the preparation of nanosuspension. Nanosuspension can be delivered by oral, parenteral, pulmonary and ocular routes. DOI: http://dx.doi.org/10.3329/ijpls.v2i4.17117 International Journal of Pharmaceutical and Life Sciences Volume 2, Issue 4: October 2013; 179-196